Aromaterapi Lavender Essensial Oil Berpengaruh Dominan terhadap Skala Nyeri 24 Jam Post Seksio Sesaria - Herlyssa Herlyssa; Jehanara Jehanara; Elly Dwi Wahyuni (Politeknik Kesehatan Tanjung Karang, 2018)
This study aims to prove the effect of Lavender Essential Oil Aromatherapy to the 24-hour pain scale of post sectio caesarea (SC) in Depok District Hospital. This research is a quasi-experimental design with pre and post-test with the control group. Samples of this study are mothers who have the pain of post-SC in hospitals Depok many as 68 people were divided into a treatment group (34 people) and control group (34 people). The technique of sampling is consecutive sampling. Before the intervention, the treatment group and the control group measured the pain scale using the Numerical Rating Scale. Treatment group was given 10% lavender essential oil aromatherapy 3 drops by using tissue media, then inhaled fragrance for 5 minutes at 10 cm distance. After 30 minutes of aromatherapy, patients assessed the scale of the pain. Aromatherapy is given only once at 24 hours post-SC. The results showed that the scale of pain post SC before giving aromatherapy in the control group was 3.82 while in the treatment group, it was 3.62. After giving aromatherapy it was found that the pain scale in the treatment group was 2.53, whereas in the control group 4.65. There was a significant difference of pain scale of 24 hours post SC between control group and treatment group. Lavender essential oil aromatherapy dominant influence on the reduction of pain scale of 24 hours post SC (p-value<0.05) as much as five times greater than those mothers who did not use aromatherapy. Lavender Essential Oil Aromatherapy can be used as one of the solutions in treating pain after sectio caesarea surgery.